Sex differences of resource utilisation and outcomes in patients with atrial arrhythmias and heart failure. Issue 7 (19th December 2019) - Ueberham, Laura; König, Sebastian; Hohenstein, Sven; Mueller-Roething, Rene; Wiedemann, Michael; Schade, Anja; Seyfarth, Melchior; Sause, Armin; Neuser, Hans; Staudt, Alexander; Zacharzowsky, Udo; Reithmann, Christopher; et al.
Abstract : Objective: Atrial fibrillation or atrial flutter (AF) and heart failure (HF) often go hand in hand and, in combination, lead to an increased risk of death compared with patients with just one of both entities. Sex-specific differences in patients with AF and HF are under-reported. Therefore, the aim of this study was to investigate sex-specific catheter ablation (CA) use and acute in-hospital outcomes in patients with AF and concomitant HF in a retrospective cohort study. Methods: Using International Statistical Classification of Diseases and Related Health Problems and Operations and Procedures codes, administrative data of 75 hospitals from 2010 to 2018 were analysed to identify cases with AF and HF. Sex differences were compared for baseline characteristics, right and left atrial CA use, procedure-related adverse outcomes and in-hospital mortality. Results: Of 54 645 analysed cases with AF and HF, 46.2% were women. Women were significantly older (75.4±9.5 vs 68.7±11.1 years, p<0.001), had different comorbidities (more frequently: cerebrovascular disease (2.4% vs 1.8%, p<0.001), dementia (5.3% vs 2.2%, p<0.001), rheumatic disease (2.1% vs 0.8%, p<0.001), diabetes with chronic complications (9.7% vs 9.1%, p=0.033), hemiplegia or paraplegia (1.7% vs 1.2%, p<0.001) and chronic kidney disease (43.7% vs 33.5%, p<0.001); less frequently: myocardial infarction (5.4% vs 10.5%, p<0.001), peripheral vascular disease (6.9% vs 11.3%, p<0.001), mild liver disease (2.0% vs 2.3%, p=0.003) or any malignancy (1.0% vs 1.3%, p<0.001), underwent less often CA (12.0% vs 20.7%, p<0.001), had longer hospitalisations (6.6±5.8 vs 5.2±5.2 days, p<0.001) and higher in-hospital mortality (1.6% vs 0.9%, p<0.001). However, in the multivariable generalised linear mixed model for in-hospital mortality, sex did not remain an independent predictor (OR 0.96, 95% CI 0.82 to 1.12, p=0.579) when adjusted for age and comorbidities. Vascular access complications requiring interventions (4.8% vs 4.2%, p=0.001) and cardiac tamponade (0.3% vs 0.1%, p<0.001) occurred more frequently in women, whereas stroke (0.6% vs 0.5%, p=0.179) and death (0.3% vs 0.1%, p=0.101) showed no sex difference in patients undergoing CA. Conclusions: There are sex differences in patients with AF and HF with respect to demographics, resource utilisation and in-hospital outcomes. This needs to be considered when treating women with AF and HF, especially for a sufficient patient informed decision making in clinical practice.